A educação infantil bilíngüe (português/inglês) na cidade de São Paulo e a formação dos profissionais da área: um estudo de caso - Fávaro, Fernanda Meirelles (2009)
This research aims to identify the current reality of infant bilingual education in 05 schools in the city of São Paulo as well as to trace the profile of 04 professionals in these schools. In order to do so, the following theoretical references were used: North American and Canadian views (Hornberg, 1991, Freeman, 1998; Lindholm-Leary, 2006 and Baker, 2006) and, especially, Latin American (Mejía, 2002) concerning the bilingual education and the training of reflective, critical and creative teachers (Shulman, 1987; Libâneo and Pimenta, 1999; Imbernón, 2000; Celani, 2001 and 2004; Altet and Perrenoud, 2001, and Batista and Batista, 2002), the paradigm of sociointeractionist teaching-learning (Vygotsky, 1930/2007 and 1934/1999) and the issue of texts that encode the school work (Bronckart 1997/1999 and 2006). Based on empirical studies (questionnaire sent to all schools of infant education, making up 39 institutions and interviews / questionnaires with a teacher from each school and national documents (Law of Guidelines and Bases - Law 9394/96, National Curriculum Reference to Infant Education and Parecer "N" Nº 01/2007 among others), I try to understand the reality of bilingual infant education in some schools in the city of São Paulo, in an attempt to answer my questions of research. It is a critical-interpretativist qualitative research (Severino, 2007) and a collective case study (Stake, 1998) in which I seek to understand the study of several cases in order to increase the comprehension of the area. The data analysis observed the thematic content (Bronckart 1997-1999) in order to seek out information in all of the responses obtained, the specific knowledge that could be part of the enunciators memory regarding the conceptions of bilingual education and that influence in the organization of infant bilingual education in each institution, showing its peculiarity. Besides identifying the background of teachers who work in infant bilingual education schools as well as understanding how the schools face it. The critical interpretativist interpretation sought to interpret the data in the light of representations from the researcher, based on the theoretical foundation. The results indicate that all institutions which took part in the research struggle to develop a program of total immersion, the target language is used 100% of the time children remain at school, especially in the initial series. Gradually, the mother tongue is introduced into the school routine in order to promote literacy and to provide access to culture and preservation of the students identity. All institutions consider the social and individual development through cultural knowledge as one of the fundamental roles of education. The 05 schools argue that they only hire graduated teachers. They also state to offer more training courses inside and outside school, however, the teachers claim not to have access to these courses. On the other hand, all teachers affirm to attend educational and/ or guidance meetings with their coordinators. I could also infer that among the roles of a teacher is to mediate knowledge and promote diverse areas of interaction